A FACILE SYNTHESIS OF (S) – (-) – PROPRANOLOL (Journal of Sciences, Islamic Republic of Iran)
A one-pot synthesis of (S)-(-)-propranolol is reported. Zn(NO3)2/(+)-tartaric acid catalyzed enantioselective synthesis of (S)-(-)-propranolol via kinetic resolution of key intermediate ?-naphthyl glycidyl ether with high optical and chemical yield.